URANYL ADSORPTION ONTO MONTMORILLONITE: EVALUATION OF BINDING SITES AND CARBONATE COMPLEXATION - Catalano J.G.; Brown Jr.G.E. (My University, 2005)
The fate and transport of uranium in contaminated soils and sediments may be affected by adsorption onto the surface of minerals such as montmorillonite. Extended X-ray absorption fine structure (EXAFS) spectroscopy has been used to investigate the adsorption of uranyl (UO22+) onto Wyoming montmorillonite. At low pH (∼4) and low ionic strength (10−3 M), uranyl has an EXAFS spectrum indistinguishable from the aqueous uranyl cation, indicating binding via cation exchange. At near-neutral pH (∼7) and high ionic strength (1 M), the equatorial oxygen shell of uranyl is split, indicating inner-sphere binding to edge sites. Linear-combination fitting of the spectra of samples reacted under conditions where both types of binding are possible reveals that cation exchange at low ionic strengths on SWy-2 may be more important than predicted by past surface complexation models of U(VI) adsorption on related montmorillonites. Analysis of the binding site on the edges of montmorillonite suggests that U(VI) sorbs preferentially to [Fe(O,OH)6] octahedral sites over [Al(O,OH)6] sites. When bound to edge sites, U(VI) occurs as uranyl-carbonato ternary surface complexes in systems equilibrated with atmospheric CO2. Polymeric surface complexes were not observed under any of the conditions studied. Current surface complexation models of uranyl sorption on clay minerals may need to be reevaluated to account for the possible increased importance of cation exchange reactions at low ionic strengths, the presence of reactive octahedral iron surface sites, and the formation of uranyl-carbonato ternary surface complexes. Considering the adsorption mechanisms observed in this study, future studies of U(VI) transport in the environment should consider how uranium retardation will be affected by changes in key solution parameters, such as pH, ionic strength, exchangeable cation composition, and the presence or absence of CO2.